PENGARUH E-MARKETING TERHADAP CITRA MEREK NAY@DAM PADA PT KREASI PUTRA SERAYU - Muhammat Rasid Ridho (Universitas Putera Batam, 2013)
Implementation of e-marketing to provide information for consumers about the product of PT Kreasi Putra Serayu .They can determine the level of e-marketing and can improve the brand image Nay@dam. Allegedly brand image Nay@dam is still not perceived well by the public, due to lack of marketing. The purpose of this study was to obtain an overview of the level of implementing e-marketing and an overview of the level of Nay@dam brand image perceived by the customer. To assess the effect of implementation of e-marketing on brand image Nay@dam. The research method used is descriptive method of analysis and verification with the customer unit PT Kreasi Putra Serayu as many as 91 customers who had been friends with Nay@dam facebook. The findings of this study is the application of e-marketing that provides information for consumers on its implementation is still less than the maximum. Implementation of e-marketing has positive and significant impact on brand image Nay@dam.